Mitochondria play a key role in oxidative stress-induced pancreatic islet dysfunction after severe burns. Issue 6 (6th June 2022) - Liu, Xinzhu; Liu, Zhaoxing; Li, Dawei; Niu, Yuezeng; Zhang, Wen; Sun, Jiachen; Zhang, Kun; Zhao, Hongqing; Li, Zhisheng; Shen, Chuan'an
Abstract : BACKGROUND: Severe burns are often complicated with hyperglycemia in part caused by pancreatic islet dysfunction. Previous studies have revealed that in diabetes mellitus, the pancreatic islet dysfunction is partly attributed to oxidative stress. However, the role and mechanism of oxidative stress in hyperglycemia after severe burns remain unclear. Therefore, the purpose of this study was to explore the level and mechanism of oxidative stress in pancreatic islets after severe burns and the antioxidant effect of sodium pyruvate. METHODS: A 30% total body surface area full-thickness burn model was established using male C57BL/6 mice. Fasting blood glucose and glucose-stimulated insulin secretion (GSIS) 24 hours post severe burns were detected. The levels of reactive oxygen species (ROS) and mitochondrial ROS of islets were detected. The activities of complexes in the mitochondrial respiratory chain of islets were measured. The main antioxidant defense system, glutaredoxin system, and thioredoxin system-related indexes were detected, and the expression of manganese superoxide dismutase (Mn-SOD) was measured. In addition, the antioxidant activity of sodium pyruvate was evaluated post severe burns. RESULTS: After severe burns, fasting blood glucose levels increased, while GSIS levels decreased, with significantly elevated ROS levels of pancreatic islets. The activity of complex III decreased and the level of mitochondrial ROS increased significantly post severe burns. For the detoxification of ROS, the expressions of thioredoxin 2, thioredoxin reductase 2, and Mn-SOD located in mitochondria decreased. Sodium pyruvate reduced the level of mitochondrial ROS in islet cells and improved the GSIS of islets after severe burns. CONCLUSION: The high level of mitochondrial ROS of islets is caused by reducing the activity of complex III in mitochondrial respiratory chain, inhibiting mitochondrial thioredoxin system, and downregulating Mn-SOD post severe burns. Sodium pyruvate plays an antioxidant role post severe burns in mice islets and improves the islet function. Abstract :